Dinosaur habitats from Upper Cretaceous eolian deposits in the Gobi desert, Mongolia - Saneyoshi, Mototaka; Tsogtbaatar, Khishigjav; Barsbold, Rinchen; Chinzorig, Tsogtbaatar; Mainbayar, Buuvei; Nishido, Hirotsugu; Ishigaki, Shinobu (Mongolian Journal of Paleontology, 2021)
The Upper Cretaceous eolian sediments in the Gobi Desert Mongolia yield a large number of dinosaur fossils with good preservation, well known as one of most important dinosaur localities in the world. Furthermore, vertebrate fossils have been extensively found from the Djadokhta Formation in these areas, where any of tephra and micro-fossils for a key of geochronological examination has not been confirmed so far. Therefore, a stratigraphic assignment of the eolian sediments should be indispensable in advancing paleontological investigations on the evolution of the dinosaurs by comparison with those reported elsewhere in the world as well as geological study in these areas.